An Inventory of CiaR-Dependent Small Regulatory RNAs in Streptococci - Jabbour, Nancy; Lartigue, Marie-Frédérique (Frontiers in Microbiology, 2021)
Bacteria adapt to the different environments encountered by rapid and tightly-controlled regulations involving complex networks. A first line of control is transcriptional with regulators such as two-component systems (TCSs) that respond to physical and chemical perturbations. It is followed by posttranscriptional regulations in which small regulatory RNAs (sRNAs) may affect RNA translation. Streptococci are opportunistic pathogens for humans and farm animals. The TCS CiaRH is highly conserved among this genus and crucial in bacterial survival under stressful conditions. In several streptococcal species, some sRNAs belong to the CiaRH regulon and are called csRNAs for cia-dependent sRNAs. In this review, we start by focusing on Streptococcus species harboring a CiaRH TCS. Then the role of CiaRH in streptococcal pathogenesis is discussed in the context of recent studies. Finally, we give an overview of csRNAs and their functions in Streptococci with a focus on their importance in bacterial adaptation and virulence.